Relação da postura craniocervical e da desordem temporomandibular com as funções estomatognáticas de alimentação - Weber, Priscila (2012)
Craniocervical posture can interfere directly on the mandibular and hyoid bone position as well as on the masticatory and swallowing functions. On the other hand a stomatognathic alteration such as temporomandibular disorder (TMD) can be a harmful factor on the alimentaires functions. This study aimed to investigate the craniocervical posture and TMD relation on the masticatory and swallowing functions. 70 women were divided according to TMD diagnostic evaluated by the Research Diagnostic Criteria (RDC/TMD): 34 with TMD and 36 without signs and symptoms of TMD. Craniocervical posture and mandibular and hyoid bone variables were measured by cephalometric analysis. Masticatory and swallowing function evaluation was performed according to a protocol of orofacial myofunctional evaluation with Scores (OMES). It was observed significant correlations between craniovertebral angle and hyoid bone position variables: linear distance from the hyoid bone to the menton (p=0,02) and to the mandible (p=0,03). The angle which measured the anterior position of the head also demonstrated a significant correlation with the linear distance between hyoid bone and jaw (p=0,00). Degree of cervical curvature showed a correlation between the linear distance from hyoid bone to the third cervical vertebra (p=0,01). An important craniocervical postural change was observed in the group although there was no association between them and a higher frequency of atypical behaviors evaluated during masticatory and swallowing functions. TMD subjects showed a significant difference on tongue (p=0,03) and lip (p=0,04) posture during swallowing. Chronic unilateral chewing pattern was also observed in the TMD group (p=0,03). In spite of the anatomical relation between craniocervical posture and mandibular and hyoid bone position it was not possible to confirm that the postural alterations observed could be associated to damages on masticatory and swallowing functions. Nonetheless, TMD presence resulted on a higher frequency of myofunctional alterations during these functions.